1998
DOI: 10.1021/ac9708250
|View full text |Cite
|
Sign up to set email alerts
|

Microfabricated Silicon Mixers for Submillisecond Quench-Flow Analysis

Abstract: Elucidation of fast chemical reactions such as protein folding requires resolution on a submillisecond time scale. However, most quench-flow and stop-flow techniques only allow chemical processes to be studied after a few milliseconds have elapsed. In order to shorten the minimum observation time for quench-flow experiments, we designed a miniaturized mixer assembly. Two “T” mixers connected by a channel are etched into a 1 cm × 1 cm silicon chip which is interfaced with a commercially available quench-flow in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(78 citation statements)
references
References 25 publications
0
77
0
1
Order By: Relevance
“…Several groups have relied on various micromachining techniques to construct mixers consisting of thin (~100 μm) channels, often using a simple T-arrangement. 71,75,79,84,91,123,124 A recent example is the microfluidic mixer design by Bilsel at al. 91 illustrated in Figure 3.…”
Section: Continuous-flow Techniquesmentioning
confidence: 99%
“…Several groups have relied on various micromachining techniques to construct mixers consisting of thin (~100 μm) channels, often using a simple T-arrangement. 71,75,79,84,91,123,124 A recent example is the microfluidic mixer design by Bilsel at al. 91 illustrated in Figure 3.…”
Section: Continuous-flow Techniquesmentioning
confidence: 99%
“…They reported no apparent shear breakage of the DNA after mixing by testing with agarose gel electrophoresis. Bökenkamp et al (1998) fabricated a silicon mixer for liquid phase chemical reactions over short durations of 110 ms. Volpert et al (1999) reported on an actively controlled micro mixer using six branched microchannels perpendicular to the main microchannel. Mixing inside the main microchannel was enhanced by introducing periodic perturbations through the side microchannels.…”
Section: Introductionmentioning
confidence: 99%
“…40). These changes in colour are generally the result of chemical reactions, and as such can be very application specific, with the advantages and disadvantages that come with that.…”
Section: Quantification Of Mixingmentioning
confidence: 99%
“…40, where a T junction was used to hydrolyse phenyl chloroacetate (PCA). Results showed that the hydrolysis reaction completed within 110 s when complete mixing was achieved.…”
Section: Y/t/x Junction Channelsmentioning
confidence: 99%